Analgesic and anti-inflammatory activities of combrang (Nicolaia speciosaHoran) stem the extract - Susilowati, Sri Sutji; Martono, Sudibyo; Riyanto, Sugeng; Nugroho, Agung Endro (Indonesian Journal of Pharmacy, 2011)
Long-term  goal  of  this  study  is  the  use  of  combrang  (Nicolaia  speciosa Horan)  as  an  ingredient  of  traditional  medicine  after  being  evaluated  through preclinical  testing  and  clinical  trials  both  extract  and  its  bioactive  compounds. This  study  includes  analgesic-antiinflammatory  activity  test  of  n-hexane, chloroform,  ethyl  acetate  and  methanol  extract  of combrang stem.  Analgesic test against crude extract of n-hexane, chloroform,ethyl acetate and methanol, using acetate writhing method. Antiinflammatory test using inhibition method of paw oedema by carrageenan induced on Wistar rats. Analgesic-antiinflammatory activity  compared  to  Na-diclofenac.  The  result  is  four  extracts  have  analgesic and  antiinflammatory  activity,  ethyl  acetate  extract  has  the  highest  analgesic and antiinflammatory activity.Key words: analgesics, anti-inflammatory, extract of combrang stem